2020
DOI: 10.9734/cjast/2020/v39i430537
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition and Bioactive Compounds in Diverse Eggplant Genotypes

Abstract: Eggplant (Solanum melongena L.) is an important solanaceous crop of tropics and sub-tropics, having high production potential, and also a rich source of nutrients, particularly, carbohydrates, proteins, dietary fibre and vitamins like thiamin, niacin, pantothenic acid and folic acid, minerals like calcium, iron, potash, zinc, copper and manganese as well as bioactive compounds. However, eggplant is available in diverse shape and colour and consumer preference varies and the nutrient composition is different. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The average ascorbic acid concentration in the different landraces ranged from 3.46 to 18.47 mg 100 g −1 FW. These values are consistent with several studies carried out on eggplant landraces (Bidaramali et al, 2020;Quamruzzaman et al, 2020). Some studies, such as Prohens et al (2014) have even found major differences between traditional varieties and commercial hybrids, meaning that, on average, landraces present higher ascorbic acid content.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The average ascorbic acid concentration in the different landraces ranged from 3.46 to 18.47 mg 100 g −1 FW. These values are consistent with several studies carried out on eggplant landraces (Bidaramali et al, 2020;Quamruzzaman et al, 2020). Some studies, such as Prohens et al (2014) have even found major differences between traditional varieties and commercial hybrids, meaning that, on average, landraces present higher ascorbic acid content.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, its analysis is recommended in eggplant, as fruits are believed to be rich in this compound and could therefore satisfy consumers (Best et al, 2010). Even though significant differences were found among the three landraces analysed in this assay, and landrace B17 stood out for its high sugar content, compared to data from other studies on eggplants (Passam and Karapanos, 2008;Hernández-Hernández et al, 2011;San José et al, 2013;Zaro et al, 2014b;Pohl et al, 2019;Bidaramali et al, 2020), it is observed that sugar concentration is almost doubled in our landraces.…”
Section: Discussionmentioning
confidence: 46%
“…Best result was obtained in T 7 (STBFR + Azotobacter @ 4 kg ha -1 +PSB @ 4 kg ha -1 ) and it was 3.87 mg 100 g -1 fresh weight. Present findings indicate that eggplants exposed to inorganic fertilizers and microbial inoculants had better fruit quality which might be due to accelerated nutrient ), T 2 -N 100 + P 100 , T 3 -N 100 + K 100 , T 4 -P 100 + K 100 , T 5 -STBFR + Azotobacter @ 5 kg ha -1 , T 6 -STBFR + PSB @ 5 kg ha -1 , T 7 -STBFR + Azotobacter @ 4 kg ha -1 + PSB @ 4 kg ha -1 , T 8 -Control acquisition by the crop and optimum rhizospheric activity (Thingujam et al, 2016;Bidaramali et al, 2020).…”
Section: Quality Parametersmentioning
confidence: 99%
“…Eggplant (Solanum melongena L.) was a Eggplant (Solanum melongena L.) was popular vegetable among the community and grows well if the nutrients were adequate (Sahid et al, 2014;Setyadi et al, 2020). Eggplant has rich nutrients, it contains of protein, carbohydrates, minerals, and vitamins such as niacin, thiamin, pantothenic acid, and folic acid (Bidaramali et al, 2020). It was good for health because it contains antioxidants, anti allergic, anti microbial, and anti cancer (Helilusiatiningsih, 2021).…”
Section: Introductionmentioning
confidence: 99%